Keragaman Komunitas Fitonematoda pada Sayuran Lahan Monokultur dan Polikultur di Sumatera Barat - Amallia Rosya; Winarto Winarto (Jurnal Fitopatologi Indonesia, 2013)
Plant parasitic nematodes can cause crop losses in celery. Parasitic nematodes that infect celery are Helicotylenchus spp., Trichodorus, Longidorus, Xiphinema and Meloidogyne spp Cropping pattern becomes part of the factors that influence the presence of plant parasitic nematodes in celery. Field obervation was conducted in celery growing areas to study the diversity and abundance of parasitic nematodes from monoculture and polyculture cropping system. Seven genus of nematodes, i.e. Meloidogyne, Pratylenchus, Tylenchorhinchus, Tylenchulus, Xiphinema, and two nonparasitic nematode were identified from polyculture cropping system, whereas 4 genus were found from monoculture cropping system i.e. Meloidogyne, Pratylenchus, Tylenchulus and Trichodorus. Genus with high abundance in polyculture cropping pattern was Xiphinema and Meloidogyne however Trichodorus was not found. Genus with a high abundance in monoculture was Meloidogyen and Xiphinema was not found. The genus most frequently found was Meloidogyne in polyculture and Xiphinema in monoculture.